DETEKSI POLA AROMA KULIT BABI DAN KULIT SAPI MENGGUNAKAN ELECTRONIC NOSE (E-Nose) - Dwi Putri, Desrinda Mala; Rakhmadi, Frida Agung; Hidayat, Shidiq Nur; Triyana, Kuwat (Sunan Kalijaga Journal of Physics, 2020)
This study aimed to detect the aroma pattern of pigskin and cow-hide using E-Nose. This research was conducted by collecting data. Data were collected using Electronic Nose (E-Nose) and GeNose datalogger software. The software only displays the stress data of the two aroma patterns of cow hide and pigskin in real time, but has not been able to display the difference between the two aroma patterns. The aroma pattern of pigskin and cow hide has been detected and the radar plot shows the performance that there is one TGS sensor that does not respond to the aroma patterns of the two skins, namely TGS 2612, while the TGS sensor that responds is seven TGS sensors.